2018
DOI: 10.1155/2018/5074923
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Sarcopenia in HIV-Infected Individuals

Abstract: Background Sarcopenia is a geriatric syndrome that leads to a loss of functionality and mortality. Methods We assessed the prevalence of sarcopenia in HIV-infected patients attended in our HIV Unit who had at least two DXA scans from 2000 to 2016 (1,720 DXA scans from 860 individuals). Sarcopenia was determinate according to appendicular skeletal muscle mass index (ASM) calculated as the ratio between skeletal muscle mass index (SMI) by DXA and height2 (kg/m2). We stratified patients by gender and age (<40, 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 23 publications
1
41
2
Order By: Relevance
“…Similarly, the prevalence of sarcopenia among 153 HIV-infected Asians was higher in those above 50 years of age compared to HIV-uninfected controls matched by age, sex and ethnicity (17% vs. 4%), but not significantly different when people below the age of 50 were included (10 vs. 6%) [33]. In a large Spanish cohort of PLWH assessed in the period 2000-2016, the overall prevalence of sarcopenia in those aged >50 years was 27.8%, with a different gender distribution, involving 43% of women and 8.8% of men [34].…”
Section: Epidemiological and Clinical Aspects Of Sarcopenia In Peoplementioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, the prevalence of sarcopenia among 153 HIV-infected Asians was higher in those above 50 years of age compared to HIV-uninfected controls matched by age, sex and ethnicity (17% vs. 4%), but not significantly different when people below the age of 50 were included (10 vs. 6%) [33]. In a large Spanish cohort of PLWH assessed in the period 2000-2016, the overall prevalence of sarcopenia in those aged >50 years was 27.8%, with a different gender distribution, involving 43% of women and 8.8% of men [34].…”
Section: Epidemiological and Clinical Aspects Of Sarcopenia In Peoplementioning
confidence: 85%
“…Some of these studies also identified specific risk factors for sarcopenia in PLWH, in addition to traditional risk factors such as female gender, increasing age and high body mass index. These included low education level and employment status, long duration of HIV infection, low CD4 + T-cell counts at the start of cART and long-time exposure to certain nucleoside reverse transcriptase inhibitors (NRTIs), i.e., zidovudine, stavudine or didanosine [27,33,34]. Finally, specific health outcomes were also analysed in relation to the presence of sarcopenia, including mortality risk scores, quality of life, healthcare utilization, functional disability and falls.…”
Section: Epidemiological and Clinical Aspects Of Sarcopenia In Peoplementioning
confidence: 99%
“…63,64 The rate of decline in muscle mass over a 5-year study period was similar in PWH and controls, 64 yet the frequency of sarcopenia increased over a 7-to 10-year follow-up in PWH older than 50 years with the progression of sarcopenia greater in women than men. 63 Standardized physical performance measures allow early detection and assessment of physical function impairments, as well as assess the effects of interventions aimed at averting physical decline and preventing mobility disability. Going beyond traditional research regarding muscle mass in PWH, we can learn more about the skeletal muscle specifically cellular and enzymatic activity changes that transpire with the use of skeletal muscle biopsies.…”
Section: Measuring Skeletal Muscle Loss In Pawhmentioning
confidence: 89%
“…Distinct from HIV wasting syndrome (characterized by overall body weight loss and diarrhea), sarcopenia is a progressive and generalized skeletal muscle disorder, and defined as a loss of both muscle mass and muscle function [8]. Some recent studies have demonstrated an increased presence of sarcopenia among PLHIV [9,10].…”
Section: Introductionmentioning
confidence: 99%